Some Properties of the Chloroplast Envelope as Revealed by Electrophoretic Mobility Studies of Intact Chloroplasts - Stocking, C. Ralph (1982)
The electrophoretic mobility of mature spinach (Spinacia oleracea L. var. Americana) chloroplasts sampled over a 7-month period was between −2.03 and −2.45 micrometers per second per volt per centimeter when suspended in a solution containing 1 millimolar CaCl(2). The surface charge density of EDTA-treated chloroplasts was calculated to be −7,400 electrostatic units per square centimeter representing, on the average, one electronic charge per 645 square Angstroms. Electrophoretic mobility increases during plastid maturation. Calcium, but not magnesium, generally stabilized the envelope of isolated plastids against small increases in surface charge that occur with time in the absence of calcium. Pronase caused a sharp, but temporary, decrease in the electrophoretic mobility of chloroplasts. This was interpreted as representing a transient binding of pronase to the envelope surface during proteolysis. No −SH groups were detected on the surface of the plastid envelope. Inasmuch as the isoelectric point of intact chloroplasts was found to be at pH 4.5, it is likely that the major part of the total surface charge results from the presence of exposed carboxyl groups of intrinsic envelope proteins that are not readily hydrolyzed by mild pronase treatment.